Evaluation of the Implementation of Merdeka Belajar Using the CIPP Model: A Case Study at SMK Negeri 2 Payakumbuh - Renol Fitria Asdi; Ahyanuardi; Indra Saputra (Jurnal Penelitian Pendidikan IPA, 2025)
The Merdeka Belajar Curriculum was launched by the Ministry of Education, Culture, Research, and Technology to improve the quality of education in Indonesia. This curriculum is designed to provide flexibility in learning, develop 21st-century skills, and instill the values of the Pancasila Student Profile. However, the implementation of the Merdeka Belajar Curriculum in Vocational High Schools (SMK) faces various challenges, such as limited resources, teacher readiness, and the involvement of the business and industrial sectors. This study aims to evaluate the implementation of the Merdeka Belajar Curriculum at SMK Negeri 2 Payakumbuh using the Context, Input, Process, and Product (CIPP) evaluation model. The evaluation was conducted to understand the application of the curriculum and identify its strengths, weaknesses, and improvement opportunities. This research uses a quantitative method with a structured approach to evaluate the implementation of the Merdeka Belajar Curriculum. Quantitative data were collected through the distribution of questionnaires designed to measure the four components of the Context, Input, Process, and Product (CIPP) evaluation model. The research sample includes teachers, students, and the principal at SMK Negeri 2 Payakumbuh who are involved in the curriculum implementation.. The research instruments consist of questionnaires, interviews, and observations designed to measure the four components of the CIPP model. The results show that the context, input, process, and product components of the Merdeka Belajar Curriculum implementation are generally good. However, the input component requires improvement, particularly regarding resource availability, ongoing teacher training, and strengthening collaboration with the business and industrial sectors. This study recommends that implementing the Merdeka Belajar Curriculum be continued by improving the input aspect through providing adequate resources, intensive teacher training, and strengthening partnerships with the business and industrial sectors to enhance curriculum relevance.